KAJIAN SIFAT DIELEKTRIK PADA NANOPARTIKEL COBALT FERRITE (CoFe2O4) YANG DIENKAPSULASI DENGAN POLYETHYLENE GLYCOL (PEG-4000) - , AJO DIAN YUSANDIKA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Nanoparticles Cobalt Ferrite (CoFe2O4) has been synthesized with various concentrations of PEG-4000 at 0, 25, 50, and 75%. The measurement uses computerized system impedance spectroscopy in the frequency region of 10 kHz to 120 kHz to investigate its dielectric behaviour caused by frequence changes and changes of concentrations PEG-4000. The result shows that the dielectric constant and loss tangent decreased with increasing frequency but the impedance increased with increasing frequency. Overall, the addition of PEG-4000 can raise the value of the real dielectric constant and can raise the value of the impedance, but it reduce of the loss tangent value. The pattern of relationships between loss tangent against frequency electric field on all sample occurred a certain maximum value at the frequency range 10 kHz - 20 kHz and the patterns of relationships between impedance against frequency electric field occurred a certain minimum value at frequency range 10 kHz - 20 kHz. In general the presence of encapsulation of PEG-4000 raises value of the real dielectric constant, raise value of the impedance, and lower value of loss tangent. This is due to encapsulation of PEG- 4000 enlarge of grain size CoFe2O4 so as to raise value of the real dielectric constant and raise value of impedance but lower the loss tangent value. Keywords: CoFe2O4 nanoparticles, the encapsulation of PEG, the dielectric constant